Chronic metformin intake and gastric cancer: A pooled analysis within the Stomach cancer Pooling (StoP) Project. (December 2022) - Sassano, Michele; Mariani, Marco; Pelucchi, Claudio; Vicente, Martín; Pinto-Carbó, Marina; Lunet, Nuno; Morais, Samantha; La Vecchia, Carlo; Pastorino, Roberta; Boccia, Stefania
Abstract: Introduction: The association between chronic use of metformin and risk of gastric cancer (GC) has been investigated with contradicting results. We aimed to study the association between chronic use of metformin and GC by using data from the Stomach cancer Pooling (StoP) Project, an epidemiological consortium of case-control studies on GC. Methods: Data from three studies of the StoP Project with available information on metformin intake were analyzed. Multivariable logistic regression models were used to estimate study-specific odds ratios (ORs) and 95% confidence intervals (CIs) for the association between chronic use of metformin and GC risk. Analyses were adjusted for sex, age, socioeconomic status, body mass index, smoking status, alcohol drinking status, and history of diabetes. Study-specific ORs and 95% CIs were then pooled with a random-effects model. The dose-response relationship between the duration of metformin intake and GC was assessed with a one-stage logistic model, and the duration of intake was modelled using second-order fractional polynomials. Results: The OR of GC in metformin users versus non-users was 1.01 (95% CI=0.61, 1.67). The association between metformin and GC did not change among different strata of study participants' characteristics or when restricting the analyses to those with a history of diabetes. The dose-response analysis showed a slightly reducing trend in the OR of GC and a borderline significant association with increasing duration of metformin intake. Conclusions: The results of our study do not clearly support an association between chronic use of metformin and GC, warranting further research. Highlights: In contrast with a number of previous studies, the overall analysis showed no appreciable association between chronic metformin use and gastric cancer. The findings were similar when stratifying according to study participants' characteristics, as well as to subsite or histological classification of gastric cancer. The association was not significant regardless of participants' previous history of diabetes. The dose-response analysis, however, suggests that metformin intake might slightly reduce the risk of gastric cancer, though confirmation by further studies is needed.